Legal Liability for Prestige Brand Parody for Ads - Nayasari, Dhevi; Nabilah, Wardatun; Tjahjani, Joejoen; Agustin, Velinsia Cindy (Universitas Islam Lamongan, 2026)
Parody of prestige brands in the context of commercial advertising has sparked complex legal debates, particularly regarding the boundary between freedom of expression and trademark protection. Prestige brands, as brands with a high reputation and strong symbolic value, are vulnerable to forms of exploitation that can harm their image and economic value. Based on the background above, the author proposes the following problem formulation: first, what is the legal responsibility of parody advertisers towards prestige brands? And second, how is the legal protection of prestige brands that are parodied for advertisement purposes? This research employs a normative legal type, with a statutory approach. The legal materials used are primary legal materials including: Law Number 20 of 2016 concerning Brands and Geographical Indications, and Law Number 28 of 2014 concerning Copyright. From the research results, it can be concluded that: the use of famous brands in parodies is not automatically protected by freedom of expression if the purpose is commercial and can mislead consumers. The perpetrators of the parody can be held legally accountable if the parody causes damage to the owner of the prestige brand, even though parody is a form of freedom of expression, its use must heed legal provisions so as not to violate the exclusive rights of the brand owner. The owner of the prestige brand has the right to demand the cessation of violations and compensation for the economic and moral damages incurred.